Qualidade da educação e gestão escolar na rede municipal de Canoas/RS: um estudo a partir do PDE-interativo - Trentin, Elisangela Krafchinski (2014)
The research, theoretical nature, focuses on the quality of education, their influences and challenges for managing school forward to the influences of administrative and pedagogical dynamics of school units in Canoas, with reference to the documentary analysis of the responses contained in the PDE-INTERACTIVE. Were analyzed survey responses online PDE-Interactive, whose main goal is to assist managers to make the "X-ray" of the school, is, about the current situation and every moment, try to identify the main problems and challenges to overcome, to this end, this research used the information provided in the dimensions: Results-axis, size 1 - Indicators and fees and Axle - Direct Intervention, size 4 - Management, theme and direction Processes. The study shows how object studies the role of school management in conjunction with the quality of education, considering the "management teams" as authors and important political actors in education in Canoas/RS. Dialogues with authors that approached educational and democratic management, highlighting authors such as Paro, Libâneo, Martins, and Colombo, among others education and quality indicators, highlight the Veiga, Saviani, Bogdan, and Botanni Bonamino authors. For reflections on the role of managers and the educational process of schools, seek Alarcão, Luck, Paro and Rangel. The theoretical rescues both national legal provisions as international, that direct indicators of Assessment Systems resulted in guidelines and policies for improving public education, considering the current situation of education requires schools to managers able to lead, ensure that the school to perform its mission, articulate educational community in the implementation of the educational project, with the prospect of participatory management of pedagogical and administrative action, and foster the educational indicators presented by the external evaluation systems serve projections for an educational restructuring and municipal policy with the focus on improving the quality of education.